Evaluation of Voltage Variations Arising from the Increase in Photovoltaic Insertion in the Transmission Network: Case Study Coremas-PB Power Plant - Fábio Xavier Lobo; Gustavo Fernandes de Negreiros; Igor Cavalcante Torres; Chigueru Tiba (Energies, 2023)
The objective of this work was to analyze the impacts on the transmission network due to the increase in centralized photovoltaic (PV) generators’ incorporation. A study was carried out in a high-voltage (HV) transmission network, considering adjustments in the simulation environment for more realistic results. ANAREDE software and the static voltage stability evaluation method were used. The simulation was carried out in a steady state, considering an average load and the power of the PV generators corresponding to the base case (70.6 MW), with an increase of 100% of the predicted total (270 MW) for the future. The results showed that, under normal and contingency conditions, small disturbances caused voltage instability. It was observed that the incorporation of PV generators contributes to the improvement of the voltage stability in the bars close to their insertion. However, the greater the PV distribution and generation was, the greater the influence on the attenuations of the voltage profiles through the transmission system was.